Ornamental values and inventorying of vegetable garden plants in decorative private gardens in the territory of the city of Knin - Boris Dorbić; Biljana Jurić-Ćivro; Željko Španjol; Emilija Friganović; Branka Ljevnaić-Mašić; Margarita Davitkovska; Zvezda Bogevska (My University, 2020)
Vegetable garden plants have always been an integral part of decorative gardens. They provide the garden with features of casualness, while simultaneously also being useful and ornamental if they are properly incorporated into the garden area. The paper presents the significance and the importance of vegetable garden as an integral part of the garden, as well as ornamental characteristics of individual vegetable garden plant types. The research segment of the paper provides inventorying of vegetable garden plant types in decorative private gardens in the territory of the city of Knin. Taxonomic analysis included 20 plant species, i.e. Angiospermae, all the species, which also includes Dicotyledonae (16; 80 %), whose share is higher than that of Monocotyledonae (4; 20 %) and they have been grouped in nine families. It is important to highlight the plant family Solanaceae that has the largest number of species (4 species).
Keywords: garden plants, ornamental characteristics, private gardens, inventorying, Knin